The Morphology of Battery Electrodes with the Focus of the Conductive Additives Paths. Issue 10 (28th July 2015) - Indrikova, Maira; Grunwald, Stephan; Golks, Frederik; Netz, Andreas; Westphal, Bastian; Kwade, Arno
Abstract : Model experiments, in which active material in the electrode is replaced with insulating ceramic particles, are used to show the importance of pure conductive additives network. Ceramic particles are chosen with particle diameter of 10 and 3 μm. Coatings with similar loading and varying levels of carbon black, graphite and polyvinylidene fluoride are fabricated, analyzed regarding electronic conductivity and investigated with a new "quasi" in-situ SEM compression method. The electronic conductivity strongly depends on porosity, inactive material amount and distribution. SEM/EDX images showed that coatings with 10 μm particles have higher porosity and denser network of conductive additives compared to 3 μm particles. Therefore, the conductive additives and binder amount should be adjusted based on the particle size distribution.